Is ultraviolet exposure acquired at work the most important risk factor for cutaneous squamous cell carcinoma? Results of the population‐based case–control study FB‐181. (15th January 2018) - Schmitt, J.; Haufe, E.; Trautmann, F.; Schulze, H.‐J.; Elsner, P.; Drexler, H.; Bauer, A.; Letzel, S.; John, S.M.; Fartasch, M.; Brüning, T.; Seidler, A.; et al.
Summary: Background : Squamous cell carcinoma (SCC) is one of the most frequent types of cancer constituting a significant public health burden. Prevention strategies focus on limiting ultraviolet (UV) exposure during leisure time. However, the relative impact of occupational and nonoccupational UV exposure for SCC occurrence is unclear. Objectives : To investigate the association between occupational and nonoccupational UV exposure for SCC in a multicentre population‐based case–control study hypothesizing that high occupational UV exposure increases the risk of SCC. Methods : Consecutive patients with incident SCC ( n = 632) were recruited from a German national dermatology network. Population‐based controls ( n = 996) without history of skin cancer were recruited from corresponding residents' registration offices and propensity score matched to cases. Lifetime UV exposure, sociodemographic and clinical characteristics were assessed by trained physicians. Occupational and nonoccupational UV exposure doses were estimated by masked investigators using established reference values. Odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were assessed using conditional logistic regression adjusting for relevant confounders. Results : Total solar UV exposure was significantly associated with increased SCC. The OR for high (> 90th percentile) vs. low (< 40th percentile) and high vs, moderate (40–59th percentile) occupational UV exposure was 1·95 (95% CI 1·19–3·18) and 2·44 (95% CI 1·47–4·06) for SCC. Adjusting for occupational UV exposure, nonoccupational UV exposure was not significantly related to SCC incidence. Dose–response relationships were observed for occupational but not for nonoccupational solar UV exposure. Conclusions : Solar occupational UV exposure is a major determinant of incident SCC. Our findings indicate that prevention strategies should be further expanded to the occupational setting. Abstract : What's already known about this topic? Ultraviolet (UV) exposure is the most important risk factor for cutaneous squamous cell carcinoma (SCC). Public health strategies mainly focus on UV‐exposure prevention in nonoccupational settings. Epidemiological studies indicated an elevated risk of SCC in outdoor workers compared with indoor workers. The relative impact of occupational and nonoccupational UV exposure concerning SCC risk is unclear. What does this study add? This population‐based case–control study was the first to apply validated UV‐exposure assessment instruments to discriminate occupational vs. nonoccupational lifetime doses. High occupational UV exposure (> 90th percentile) is associated with a twofold increased risk for cutaneous SCC, whereas high nonoccupational UV exposure did not appear to be an independent risk factor for SCC. Prevention strategies need to be further expanded in occupational settings to tackle the burden of SCC. Linked Comment: von Schuckmann. Br J Dermatol 2018;178 :325–326 . Plain language summary available online